1996
DOI: 10.1046/j.1365-2141.1996.452992.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum erythropoietin in chronic lymphocytic leukaemia

Abstract: Anaemia is a frequent complication of advanced chronic lymphocytic leukaemia (CLL) and several cytokines known to inhibit erythropoietin (Epo) formation are produced by CLL B cells. Therefore we measured serum Epo levels in 47 CLL patients to determine whether Epo was a significant factor in the development of their anaemia. Epo levels were increased compared to normal individuals and this elevation appeared adequate for the degree of anaemia. The slope of the regression of Epo versus haemoglobin (Hb) was simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 9 publications
0
18
0
3
Order By: Relevance
“…In the U.S., more than 100,000 new cases of blood-related cancers are diagnosed every year (see The Leukemia and Lymphoma Society's web page, www.leukemia.org). Leukemia and lymphoma cells, which are of hematopoietic origin, overexpress the TfR compared with normal tissues (6,9,14,15) and may be especially sensitive to the cytotoxic effect of anti-TfR. Furthermore, it is possible that tumor-specific cytotoxicity can be enhanced by using anti-human TfR IgG3-Av to deliver biotinylated cytotoxic molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the U.S., more than 100,000 new cases of blood-related cancers are diagnosed every year (see The Leukemia and Lymphoma Society's web page, www.leukemia.org). Leukemia and lymphoma cells, which are of hematopoietic origin, overexpress the TfR compared with normal tissues (6,9,14,15) and may be especially sensitive to the cytotoxic effect of anti-TfR. Furthermore, it is possible that tumor-specific cytotoxicity can be enhanced by using anti-human TfR IgG3-Av to deliver biotinylated cytotoxic molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In normal tissues, constitutive expression of the TfR is limited to the liver, epidermis, intestinal epithelium, vascular endothelium of brain capillary, and certain populations of blood cells in the bone marrow (5)(6)(7)(8)(9). In contrast, high levels of TfR expression have been identified on many tumors (5,(10)(11)(12)(13)(14)(15). In fact, studies have shown that the TfR is expressed more abundantly in malignant tissues than their normal counterparts (5,13,16,17).…”
mentioning
confidence: 91%
“…The significance of this is unclear. On the one hand, sTfR levels are not increased beyond what is expected if the bone marrow is capable of responding adequately to an appropriate Epo stimulation for the degree of anemia [17]. This would indicate that the pathogenesis of anemia in CLL is in large part related to hemolysis and/or hypersplenism.…”
Section: Soluble Tfr As a Tumor Markermentioning
confidence: 97%
“…Children with acute leukemia or solid tumors have adequate Epo production but profoundly suppressed erythropoiesis [16]. Patients with chronic lymphocytic leukemia (CLL) appear to have appropriate Epo production and erythroid marrow response for the degree of anemia, although erythropoiesis may become impaired in advanced stages [17]. A significant proportion of multiple myeloma patients has relative marrow failure in large part due to inadequate Epo production [18].…”
Section: Soluble Tfr and Pathophysiology Of Anemiasmentioning
confidence: 99%
See 1 more Smart Citation